Dukungan Orang Tua dan Resiliensi Akademik Mahasiswa dalam Perspektif Islam - Zuniar Risanti Pratiwi; Karimulloh Karimulloh; Dewi Kumalasari (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
The virtue of people who study, including college students, in Islam is so great that the fishes in the ocean beg for forgiveness for them. However, the many academic demands faced by students can make them experience stress, anxiety and depression, so they need to be academically resilient. Parents are responsible people and will be held accountable by Allah SWT in educating their children. Parents play an important role in building children’s academic resilience as well. This study aimed to determine how parental support and academic resilience according to Islamic view. The method used in this research is a literature review by analyzing the verses of the Qur'an, hadith and relevant references. The results showed that parental support is essential in making students survive amid academic difficulties they face by providing examples, guidance, advice and Islamic education to their children. Keutamaan penuntut ilmu, termasuk mahasiswa sangat besar di dalam Islam sehingga ikan-ikan di lautan memintakan ampun baginya, tidak terkecuali mahasiswa. Namun banyaknya tuntutan akademik yang dihadapi mahasiswa, berpotensi membuat mereka mengalami stress, kecemasan hingga depresi sehingga memerlukan resiliensi akademik. Orang tua adalah orang yang bertanggung jawab dan akan dimintai pertanggung-jawaban oleh Allah SWT dalam mendidik anaknya. Orang tua juga memainkan peranan penting dalam membentuk resiliensi akademik anak. Penelitian ini bertujuan untuk mengetahui bagaimana dukungan orang tua dan resiliensi akademik menurut perspektif Islam. Metode penelitian ini adalah dengan menggunakan studi pustaka dengan menganalisis dari ayat-ayat Al-Qur’an, hadits dan referensi yang relevan. Hasil yang didapatkan bahwa kehadiran dukungan orang tua sangat penting dalam membuat mahasiswa tetap bertahan di tengah kesulitan akademik yang dihadapinya dengan cara memberikan contoh teladan, bimbingan, nasehat dan pendidikan Islam kepada anak-anaknya.